Pertubuhan Peladang kawasan Kampong Pelet goat farm project feasibility study / Mohamad Salihin Abdul Rasid - Abdul Rasid, Mohamad Salihin (2014)
Goat can be defined as any of numerous agile, hollow-horned ruminants of the genus Capra aegragus, of the family Bovidae, closely related to the sheep, found native in rocky and mountainous regions of the Europe, Asia and Persian (goat, n.d.). Goats are one of the oldest domesticated species. Goats have been used for their milk, meat, hair, and skins over much of the world. Goats survive by eating wild plants in the mountains and hills. Once tamed, these animals brought by humans to various parts of the world until now is available in almost all countries of the world (Abdul Razak Alimon 1990). Goat farming is one of the main agricultural activities in Malaysia. These animals are much bred in the villages, rubber and palm oil estates, rice fields and vacant land. Small farmers breed goats for different purposes. Goat farming is not limited only economically, but this animal is important in terms of socio-agriculture of the farmers for many years (Devendra 1982).